The Relationship Between Obstructive Sleep Apnea And Levels Of Depression And Anxiety In Young Adults - Kanti Yunika (Faculty of Medicine, Diponegoro University, 2022)
ABSTRACTBackground: Obstructive sleep apnea (OSA) is one of the most common and serious sleep disorders that can cause various neurocognitive disorders such as depression and anxiety. OSA can occur in young adults, whom are in an important developmental age in human life. The relationship between OSA and levels of depression and anxiety has never been studied in young adults, especially college students. Early identification and treatment is expected to have an impact on better quality of life and productivity..Aim: To determine the relationship of OSA with levels of depression and anxiety in young adultsMethods: An observational study with a cross sectional design. Data were obtained from Berlin questionnaire, Zung Self-Rating Depression Scale and Zung Self-Rating Anxiety Scale which were filled out in September-November 2021. Bivariate analysis of OSA's relationship with depression and OSA with anxiety was tested using chi-square test. Multivariate logistic regression analysis was performed to test for confounding variables.Results: There was a significant relationship between OSA and depression (p=0,000, OR 4.07) and OSA and anxiety (p=0,000, OR 4.5) in young adults. Logistic regression analysis showed that gender was a confounding variable of anxiety (p=0.044) in young adults.Conclusion: There is a significant relationship between OSA and levels of depression and anxiety in young adults. Young adults who have OSA are 4.07 times more likely to be depressed than young adults who don’t have OSA. Young adults who have OSA are 4.5 times more likely to experience anxiety than young adults who don’t have OSA. There is a significant relationship between OSA and the level of anxiety controlled by the confounding variable, namely gender.